Ionic Conductivity of Nanopores with Electrically Conductive Surface: Comparison Between 1D and 2D Models. Issue 10 (3rd September 2021) - Krom, Artur I.; Ryzhkov, Ilya I.
Abstract: Nanoporous membranes with high ionic conductivity are advantageous in such electrochemical processes as (reverse) electrodialysis, capacitive deionization, and hydrogen energy conversion. In membranes with electrically conductive surface, the conductivity can be regulated by varying the surface potential. This work is devoted to the theoretical study of switchable ionic conductivity. The transport of ions is described by the 2D space charge model and 1D uniform potential model taking into account the Stern layer. The conductivity decreases with lowering the Stern layer permittivity due to enhanced screening of electronic surface charge. The growth of surface potential leads to the conductivity enhancement due to accumulation of more counter‐ions inside the nanopore. For nanopores with constant surface charge density, the ionic conductivity follows the bulk electrolyte conductivity at high ion concentrations, and becomes independent of concentration when the latter is low. In contrast, the nanopores with constant surface potential demonstrate a linear decrease of conductivity with lowering the logarithm of ion concentration. The deviation between 1D and 2D models becomes noticeable at higher values of Stern layer permittivity, pore radius, electrolyte concentration, and surface potential. The proposed models are verified by comparison with experimental data on pure water conductivity in charged porous matrix. Abstract : The ionic conductivity of nanopores with electrically conductive surface is investigated using 2D space charge and 1D uniform potential models. The limitations of 1D model are identified by analyzing the dependences of conductivity on Stern layer permittivity, pore radius, electrolyte concentration, and surface potential. The models correctly describe the experimentally observed conductivity enhancement of pure water in charged porous matrix.